2020
DOI: 10.2116/analsci.19p419
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Residual Silanol in Solid Phase Extraction of Copper to Octadecylsilyl Silica in the Presence of Acetylacetone

Abstract: Batchwise studies have demonstrated that the retention of acetylacetone (Haa) from an aqueous phase in non-endcapped octadecylsilyl (ODS) silica with silanol intentionally left (NEC) is stronger than the retention in endcapped ODS silica under ambient pressure, due to the enhanced wettability and the contribution of adsorption to silanol (-SiOH), as well as the distribution into the ODS phase. Equilibrium analysis on solid phase extraction (SPE) of copper ion with Haa to NEC has indicated the adsorption of 1:1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In the retention of acetylacetone and its metal complex from the aqueous phase on the ODS phase, it was reported that the residual silanol group improves the wettability of the ODS phase and is the donor of the ligand and the metal complex. 25 In this study, a series of compounds with and without basic hetero atoms (nitrogen or oxygen) were retained on ODS silicas of varying characteristics. The effects of the silica pore size, the type and the density of ODS group and the end-capping on the performance of ODS silica as an extracting medium were evaluated from equilibrium points of view.…”
Section: Introductionmentioning
confidence: 99%
“…In the retention of acetylacetone and its metal complex from the aqueous phase on the ODS phase, it was reported that the residual silanol group improves the wettability of the ODS phase and is the donor of the ligand and the metal complex. 25 In this study, a series of compounds with and without basic hetero atoms (nitrogen or oxygen) were retained on ODS silicas of varying characteristics. The effects of the silica pore size, the type and the density of ODS group and the end-capping on the performance of ODS silica as an extracting medium were evaluated from equilibrium points of view.…”
Section: Introductionmentioning
confidence: 99%